Gestión administrativa de la Clínica “Frío Autos” de la ciudad de Babahoyo en el periodo 2022. - León Cabeza, Jordy Andrés (2023)
Currently, business administrative management is comprised of those activities aimed at improving the productivity and competitiveness of a business. Therefore, it is of great importance to analyze how the administrative management of the "Frío Autos" Clinic in the city of Babahoyo has developed during the period 2022. Among the objectives of this research is to determine how the administrative management of the "Frío Autos" Clinic has affected the company's growth. In turn, this case study aims to establish the importance of knowledge about business administration that allows owners and future entrepreneurs who want to have their own business and expand their profits in the local market. It is concluded that Clínica Frío Autos should create effective strategies related to the work environment, control of its records, personnel training and above all, keep its objectives clear, precise and achievable by all its collaborators.